Using alternative dispute resolution for managing disputes in joint venture construction projects in Malaysia - Maidin, Ainul Jaria (2009)
Construction industry is an important aspect of any countries economic development of as it is essential for creating industrial and social infrastructure. There are various methods deployed in construction industry in order to carry our construction projects successfully. Joint ventures are common phenomenon as it enable partnership or conglomerate formed either by individuals, business entities, corporations usually to share risk or expertise needed to successfully carry out project. JV is an association between two or more parties that combines and pool their respective expertise, financial resources, skills, experience, include equipment or intellectual property such as software, patents, and knowledge in the furtherance of a particular project or undertaking or a combination of all. JV's can generally be created for a single activity or project, and can be for a long or limited time span. JV's could be useful in times of global economic downturn and many parties tend to embark on JV projects to lessen the risks involved in their undertakings. The issue is that conflict and disputes are unavoidable due to the complex nature of the construction industry and the involvement of many parties in the contractual chain, adversarial relationship, uneven risk allocation and uneven bargaining power. Construction contracts very often contain specific clauses on arbitration of disputes, however, litigation and arbitration processes can be very expensive and parties are often faced with high legal fees. This article seeks to examine the viability of other mechanisms of Alternative Dispute Resolution Processes as an addition to the litigation and arbitration in the Malaysian construction industry which are currently prevalent in resolving disputes.